1994
DOI: 10.1103/physrevb.50.8996
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond time-resolved spectroscopy of soft modes in structural phase transitions of perovskites

Abstract: Femtosecond time-domain observations of soft-mode dynamics in crystals near structural phase transitions have been conducted. Impulsive stimulated Raman scattering (ISRS) experiments are reported for both the orthorhombic phase of KNb03 and the tetragonal phase of BaTi03. The data from potassium niobate clearly show a heavily damped soft mode of B2 symmetry and relaxational modes of A & symmetry but not B& symmetry. Similarly, the data from barium titanate clearly show a heavily damped Esymmetry soft mode and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 41 publications
1
44
1
Order By: Relevance
“…Inelastic light scattering results [21,22,23] complexified this picture, by evidencing a "central peak" owing to a relaxational mode, in O-, T-KNbO 3 , T-and C-BaTiO 3 . This mode was interpreted from the 8-sites model as due to thermally activated jumps between unsymmetrical [22,23] positions of the Ti or Nb atoms.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Inelastic light scattering results [21,22,23] complexified this picture, by evidencing a "central peak" owing to a relaxational mode, in O-, T-KNbO 3 , T-and C-BaTiO 3 . This mode was interpreted from the 8-sites model as due to thermally activated jumps between unsymmetrical [22,23] positions of the Ti or Nb atoms.…”
mentioning
confidence: 89%
“…This mode was interpreted from the 8-sites model as due to thermally activated jumps between unsymmetrical [22,23] positions of the Ti or Nb atoms.…”
mentioning
confidence: 99%
“…The problem of the low-frequency E-symmetry mode in tetragonal BTO was carefully studied by polariton Raman technique reviewed by Nakamura [54] who strongly supported its displacive (oscillatory) picture even though it is strongly overdamped in the limit of short polariton wavelengths. The low-frequency modes of both symmetries were also carefully studied by Dougherty et al [55] using impulsive stimulated Raman scattering. They have accurately determined the overdamped E-symmetry soft-mode parameters, i.e.…”
Section: Tetragonal Ferroelectric Phasementioning
confidence: 99%
“…The clamped ε c a response decreases on heating monotonically to about 1400 near 125 • C [56] or to still smaller values [46]. Similar behavior follows from the phonon contribution [51,55]. Appearance of any mode softening and/or central-mode dispersion is therefore possible only very close to T C and the increase in the clamped permittivity from the ferroelectric side was never quantitatively evaluated, since it might appear only very close to T C (5-10 K).…”
Section: Tetragonal Ferroelectric Phasementioning
confidence: 99%
“…The interaction with below-bandgap excitation has been intensively studied, revealing an impulsive stimulated Raman scattering process (ISRS) for the excitation of the lattice. Dougherty and coworkers [20,21] have shown that the selective excitation of transverse optical phonons shows the signature of mode softening close to the phase transition.…”
Section: Laser-induced Lattice Changesmentioning
confidence: 99%